Clinical presentation and bacteriological profile of diabetic foot in Eastern Bihar, India - Pankaj, Deepak; Muni, Sweta; Jha, Indudhar Narayan; Kumari, Alka (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes is a worldwide problem. A majority of diabetic patients develop foot ulcers in one point of time or other during the course of their illness. Chronic wound, especially non-healing types are the most common surgical conditions. The etiopathogenesis of diabetic foot lesions are multi-factorial like diabetic neuropathies, vasculopathy, poor control of diabetes and bacterial infection. The aim of the present study was to study various modes of presentation and microbiological profile in management of diabetic foot. Methods: 100 diagnosed cases of diabetic foot were studied over a period of three years in the department of General Surgery at Katihar Medical College with emphasis on clinical features and microbiological picture of diabetic foot and its complications. Results: Males are more prone to surgical complications three times than females because of more outdoor activities. It is more prevalent in age group 51-60 years (36%). In the present study, cases presenting with ulcer were maximum (52%) followed by cellulitis (20%), cases presenting with gangrene of toe or foot was minimum (12%). Staphylococcus Aureus was found in majority of cases of septic lesions on culture of pus (41%). Other organisms isolated were Pseudomonas, Klebsiella, E.Coli, Proteus etc. Conclusions: Diabetic foot has varied presentation. The prevalence of diabetes mellitus and its surgical complications can be attributed to poor patient knowledge, education and awareness of the disease. Patient education for care of feet such as pairing of nails, wearing proper footwear and prompt reporting to doctor in case of early lesions is essential.